2012
DOI: 10.1089/nat.2011.0312
|View full text |Cite
|
Sign up to set email alerts
|

Local Delivery of Chitosan/VEGF siRNA Nanoplexes Reduces Angiogenesis and Growth of Breast CancerIn Vivo

Abstract: Vascular endothelial growth factor (VEGF) is the important angiogenic factor associated with tumor growth and metastasis in a wide variety of solid tumors. The aim of this study is to investigate the tumor suppressive effect of chitosan/small interfering RNA (siRNA)-VEGF nanoplexes in the rat breast cancer model. Chitosan/siRNA nanoplexes (siVEGF-A, siVEGFR-1, siVEGFR-2) and NRP-1 were prepared in a 15 to1 ratio and injected (intratumorally) into the breast-tumor-bearing Sprague-Dawley rats. Tumor volumes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 44 publications
2
28
0
1
Order By: Relevance
“…Notably, we have identified VEGF-A-mediated angiogenesis as one critical determinant of the increased tumorigenicity of cells undergoing EMT: (i) VEGF-A and several other angiogenic factors and cytokines are upregulated in murine breast cancer cells during EMT, (ii) CSCs of human primary breast cancers or from a human breast cancer cell line also display increased levels of VEGF-A, (iii) VEGF-A is required for the increased tumorigenicity of cells undergoing EMT, yet (iv) VEGF by itself is not sufficient to promote tumorigenicity of epithelial cancer cells, indicating that additional angiogenic factors regulated in their expression during EMT are critical for an effective tumor initiation. Our results also show that VEGF-A is required for EMT-induced angiogenesis in the early events of tumor initiation, in line with similar results in skin and brain (17) and with an established central role for VEGF-A in tumor progression (22)(23)(24).…”
Section: Discussionsupporting
confidence: 90%
“…Notably, we have identified VEGF-A-mediated angiogenesis as one critical determinant of the increased tumorigenicity of cells undergoing EMT: (i) VEGF-A and several other angiogenic factors and cytokines are upregulated in murine breast cancer cells during EMT, (ii) CSCs of human primary breast cancers or from a human breast cancer cell line also display increased levels of VEGF-A, (iii) VEGF-A is required for the increased tumorigenicity of cells undergoing EMT, yet (iv) VEGF by itself is not sufficient to promote tumorigenicity of epithelial cancer cells, indicating that additional angiogenic factors regulated in their expression during EMT are critical for an effective tumor initiation. Our results also show that VEGF-A is required for EMT-induced angiogenesis in the early events of tumor initiation, in line with similar results in skin and brain (17) and with an established central role for VEGF-A in tumor progression (22)(23)(24).…”
Section: Discussionsupporting
confidence: 90%
“…It is known that chitosan oligosaccharides 48 and chitosan nanoparticles formulated with mismatched siRNA 49 or with tripolyphosphate 50 can inhibit cancer. One study, 51 even found that chitosan nanoparticles induce greater toxicity to cancer cells than free chitosan.…”
Section: 35mentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF) and transforming growth factor-α (TGF-α) are upregulated in many tumors. Intratumor injection of chitosan/siRNA nanoplexes (siVEGF-A, siVEGFR-1, siVEGFR-2) along with NRP-1 into breast-tumor-bearing rats results in reduction in tumor volumes of up to 97 % [78]. …”
Section: Sirna For Breast Cancer Therapymentioning
confidence: 99%
“…Another class of nanoparticles based on biodegradable chitosan was developed for siRNA delivery [78]. Chitosan and its derivatives have been considered as a promising siRNA transporter with low toxicity, good biodegradability and biocompatibility.…”
Section: Recent Advances In Non-viral Delivery Vectors For Sirna Imentioning
confidence: 99%